Labour Market Transitions of Young People during the Economic Crisis - Sebastian Leitner; Robert Stehrer (The Vienna Institute for International Economic Studies (wiiw), 2014)
Abstract This paper analyses the impacts of the crisis on various groups in the labour market, providing a comparison across groups of EU countries and individual Central and East European new EU Member States. Particularly it reports how the crisis affected the transitions of people between different states in the labour market employment, unemployment, education and inactivity. Based on EU SILC data, a descriptive overview concerning the changes in transition rates is provided by estimating Markov transition probabilities. This is complemented by a set of probit regression results pointing towards significant changes in the various transitions triggered by the crisis. This is particularly the case for the younger age cohorts and low-educated workers.
Keywords: E24; J23; J63; 330; labour market transitions; crisis effects; young cohorts